Chemical applications of magnetic resonance - Dwek, R (1966)
The electron-nuclear Overhauser effect on spin ½ nuclei in solutions containing free radicals has been calculated from a method based on treatment used by Solomon. The magnitude and sign of the enhancement of the nuclear signal, which may be represented by a factor ρ depends on the nature and time dependence of the the electron-nuclear signal, which is assumed to be either dipolar or scalar. The time dependence for the dipole-dipole interactions is assumed to arise from the translational diffusion of the free radicals and the molecule containing the nuclei. three models are employed for the scalar interactions. In the first of these, termed the Sticking Model, the scalar interaction is assumed to be finite only while a molecule and free radical are "stuck" together. Thus sticking time is assumed to be short in comparison with the diffusional correlation time. However, an alternative model in which this assumption is not made has been postulated to explain certain experimental results. This is termed the Modified Sticking Model. In the third model, called the Diffusion Model, the hypothesis is made that the scalar interaction is a very short range interaction with magnitude ℏ B(d/R) exp. [-λ(r-d)]. where λ d ≫ 1, B and λ are constants, R is the distance between a nucleus and an electron, and d is the distances of the closest approach, inside of which the interaction is zero. In this model the time dependence of the scalar interaction, as in the case of the dipolar interactions, arises from the relative diffusion of the molecules and free radicals in the solution. For all the models of the scalar interaction, ρ may be plotted as a function of wsτc where ws is the electron Larmor frequency and τc the correlation time and it is found that the sign of ρ may change. The product wsτc may be altered by working at different magnetic fields or changing ρc. From measurements, at two different magnetic fields, of the nuclear spin-lattice relaxation times, the concentration of free radical in the solution and ρ, the theories allow the calculation of the mean diffusion coefficient of the radicals and molecules in solution, the correlation times and the measure of the relative importance of scalar and dipolar interactions. Experiments on fluorinated and protonic solvents containing the radical tri-tert-butyl phenoxyl (T.T.B.P) have been carried out at two different magnetic fields. The proton-free radical interactions may be explained in terms of dipole-dipole interactions. On the other hand with fluorine nuclei scalar coupling does seem to be important. The Sticking Model does not successfully describe the effect of this coupling. The other models give reasonable values for the calculable parameters, but it is difficult to decide unambiguously between them. If scalar coupling does occur, a scalar shift of the nuclear resonance is expected. this has been observed for hexaflourobenzene solutions containing T.T.B.P. The theoretical and experimental results are compared, and while either theory might explain the observed shift, less assumptions have to be made in using the Diffusion Model. The correlation time dependence of the Overhauser effect has also been studied for two systems, hexafluorobenzene and 1-1-1-trichloro-2-2-2-trifluoro-ethane, at two magnetic fields. The correlation times were altered by addition of carbon disulphide or a chlorinated hydrocarbon or by changing the temperature of the sample. Qualitatively the Diffusion Model was in best agreement with the experimental results, but quantitatively, neither model was satisfactory. In the Diffusion Model, the assumption λd≫1 is made and in an attempt to obtain better agreement with the experimental results ρ has been calculated using different values of λd in thescalar interaction function. The best agreement between experiment and theory was for values of λd≫ 1000. Measurements of the proton electron Overhauser effect can usually be interpreted in terms of dipolar interactions (positive ρ) between the electrons and the protons. However for the resonances of the tert-butyl groups of tri-tert-butyl phenol in solutions of T.T.B.P. ρ is negative. This has been shown to be associated with the proton exchange between the radical and phenol molecules. It is postulated that in the radical molecule the scalar coupling between the electron and the tert-buyl protons, occurs at least in part by a hyperconjugative mechanism. the random rotation of these tert-butyl groups could modulate this scalar coupling. This would lead to a positive polarization of the tert-butyl protons, which persists when the radical accepts a proton and becomes a tri-tert-butyl phenol molecule.